Homodyne detection of short-range Doppler radar using a forced oscillator model - Kunanon Kittipute; Peerayudh Saratayon; Suthasin Srisook; Paramote Wardkein (My University, 2017)
This article presents the homodyne detection in a self-oscillation system, which represented by a short-range radar (SRR) circuit, that is analysed using a multi-time forced oscillator (MTFO) model. The MTFO model is based on a forced oscillation perspective with the signal and system theory, a second-order differential equation, and the multiple time variable technique. This model can also apply to analyse the homodyne phenomenon in a difference kind of the oscillation system under same method such as the self-oscillation system, and the natural oscillation system with external forced. In a free oscillation system, which forced by the external source is represented by a pendulum with an oscillating support experiment, and a modified Colpitts oscillator circuit in the UHF band with input as a Doppler signal is a representative of self-oscillation system. The MTFO model is verified with the experimental result, which well in line with the theoretical analysis.
Keywords: Colpitts oscillator; Oscillation (cell signaling); Forced oscillation; Direct-conversion receiver; SIGNAL (programming language); Advanced Photonic Communication Systems